BOOK REVIEW: Marcus Plested, ‟Wisdom in Christian Tradition: The Patristic Roots of Modern Russian Sophiology”. Oxford: Oxford University Press, 2022, 274 p. - BRADSHAW, David (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
The Sophiology of Soloviev, Florensky, and Bulgakov has always had an ambivalent relation to patristic tradition. Soloviev frankly averred that his own sources lay primarily in the esotericism of authors such as Paracelsus, Boehme, and Swedenborg. Florensky, although clearly indebted to Soloviev, nonetheless made a deter¬mined effort to claim a patristic line¬age for his own teaching about Sophia. This ten¬dency culminated in Bulgakov, who (especially in his later works) repeatedly and emphatically claimed that his teaching about Sophia was in line with the best of the patristic tra¬dition. In the present work, Marcus Plested undertakes to assess the accuracy of such claims. In the process, he offers an evaluation of both the strengths and weaknesses of Sophiology as seen from an Orthodox standpoint. The work concludes with a “framework for a re-oriented sophiology” that seeks to develop biblical and patristic teaching about wisdom in a way that is both grounded in Orthodox tradition and open to Sophiology’s legitimate insights.